A retrospective analysis of the relationship between facial injury and mild traumatic brain injury. Issue 5 (1st August 2017) - Abdul Razak, Nurliza; Nordin, Rifqah; Abd Rahman, Normastura; Ramli, Roszalina
Abstract: Background/Aims: The association between facial injury characteristics and mild traumatic brain injury (mTBI) is unclear. The aim of this study was to determine the association between facial injury characteristics and mTBI. Methods: A retrospective review utilizing patients' medical records at the Universiti Kebangsaan Malaysia Medical Centre (UKMMC), Kuala Lumpur, Malaysia, was performed. Records of subjects with a history of facial trauma from 1 April 2012 to 31 December 2012 were selected. Various levels and surgical speciality records were reviewed to ascertain the diagnoses of facial injuries and mTBI. Results: A total of 348 medical records with the diagnosis of facial injuries were included. The prevalence of mTBI among these patients was 41.4% (95% CI 36.2‐46.6). The majority of the patients with mTBI were in the age group of 18‐25 years old. Patients with or without facial lacerations that were located on the lower face had a significant association with mTBI, P =.001, compared to other types of soft tissue injury. In addition, a statistically significant association was observed between facial fractures occurring to the middle face and mTBI, P =.018. Pearson chi‐square test also showed statistically significant association between the severity of facial injuries and mTBI, P =.018. Conclusions: Mild traumatic brain injury should be suspected in patients with facial injuries and particularly those with lower face lacerations, midface fractures, moderate to severe facial injury and presence of multiple injuries.